A fluorescent turn-on low dose detection of gamma-radiation based on aggregation-induced emission1. Issue 18 (4th March 2015) - Dong, Xiaobiao; Hu, Fang; Liu, Zitong; Zhang, Guanxin; Zhang, Deqing
<x xml:space="preserve">Abstract</x> A new sensitive fluorescence turn-on detection of gamma-radiation is reported by taking advantage of AIE property of the tetraphenylethylene unit and the cascade radiochemical and protonation reactions.